Non-typhoidal Salmonella bacteraemia: Epidemiology, clinical characteristics and its' association with severe immunosuppression - Fatt Quek; Dhanoa Amreeta (BMC, 2009)
Abstract Background Non-typhoidal Salmonella (NTS) is increasingly recognized as an important pathogen associated with bacteraemia especially in immunosuppressed patients. However, there is limited data specifically describing the clinical characteristics and outcome amongst the immunosuppressed patients. Methods A total of 56,707 blood culture samples and 5,450 stool samples were received by the microbiology laboratory at a tertiary referral hospital in Malaysia, during a 4-year study period. Out of these samples, 55 non-duplicate NTS isolates were identified from blood and 121 from stool. A retrospective analysis of the 55 patients with NTS bacteraemia was then conducted to determine the predominant NTS serovars causing bacteraemia and its' blood invasive potential, epidemiological data, clinical characteristics and antimicrobial susceptibility. Patients were then grouped as immunosuppressed and non-immunosuppressed to determine the association of severe immunosuppression on clinical features. Data was analyzed using the Statistical Package for Social Sciences (SPSS version 15.0) using the non-parametric Mann-Whitney test, Fisher's exact test or Chi-squared test. The odds ratio (OR) and its 95% confidence intervals (CI) were calculated. The P-value < 0.05 (two-tailed) was taken as the level of significance. Results Out of 55 NTS bacteraemia cases identified, 81.8% (45/55) were community-acquired. Salmonella enterica serovar Enteritidis had the highest blood invasiveness. An extra-intestinal focus of infection was noted in 30.9% (17/55) of the patients, most commonly involving the lungs and soft tissue. 90.9% (50/55) of the patients had an underlying disease and 65.5% (36/55) of the patients had severe clinical immunosuppressive condition with malignancy and HIV being the most common. Immunosuppressed patients had higher mortality (P = 0.04), presented more commonly with primary bacteraemia (P = 0.023), leukopenia (P = 0.001) and opportunistic infections (P = 0.01). In contrast, atherosclerotic conditions (P = 0.015), mycotic aneurysms (0.037) and gastroenteritis (P = 0.03), were significantly more common in the non-immunosuppressed patients. The non-immunosuppressed group also had a higher proportion of older patients (>50 years) with a significantly higher median age (64 versus 36.5 years; p = 0.005). Conclusion Patients with severe clinical immunosuppression had higher mortality, presented more commonly with primary bacteraemia, leukopenia and opportunistic infections and absence of gastroenteritis. Early identification and prompt medical treatment can be life saving because of the high mortality and morbidity associated with this disease especially in the immunosuppressed patients.